Checklist of ectoparasites of cricetid and heteromyid rodents in México - Light, Jessica E.; Durden, Lance A.; OConnor, Barry M.; Preisser, Whiteny C.; Acosta, Roxana; Eckerlin, Ralph P. (THERYA, 2020)
We present an updated checklist of ectoparasite species (including mites, ticks, lice, and fleas) infesting cricetid and heteromyid rodents (Rodentia: Cricetidae and Heteromyidae) in Mexico. For each parasite species, we include information on parasite taxonomy, host associations, collection localities, citations from the literature, and museum collections, when available. We recorded more than 172 mite, 114 flea, 22 tick, and 22 louse species from a minimum of 110 host species (82 cricetid and 28 heteromyid species) distributed across 31 states in Mexico. This work represents the most up-to-date and comprehensive checklist of ectoparasite species parasitizing cricetid and heteromyid rodents in Mexico.